CHARACTERIZATION OF NEW SUGAR SORGHUM VARIETIES (SORGHUM BICOLOR (L.) MOENCH) FOR GRAIN AND SUGAR YIELD UNDER TWO GROWING CONDITIONS IN THE SUDANO-SAHELIAN ZONE OF SAMANKO, MALI - Kansaye, Aly; Nebié, Baloua; Kansaye, Laya; Nantoiallah, Eugénie; Dicko, Gaoussou; Niangaly, Ousmane (International Journal of Scientific Research and Management (IJSRM), 2023)
Sorghum (Sorghum bicolor) constitutes a food source for millions of people. Nowadays, sweet sorghums have the same interest as sugarcane. Traditional sweet sorghums have a high level of juice and sugar but a low grain yield. New sweet sorghum varieties have been developed by ICRISAT. In order to evaluate the effect of phosphorus on some agronomic and biochemical parameters of these new varieties, a study entitled "Characterization of new sweet sorghum varieties (Sorghum bicolor (L.) Moench) for their grain and sugar yield under two growing conditions in the Sudano-Sahelian zone of Samanko, Mali" was carried out. The trial was set up in an alpha lattice design with 2 replications. The treatments consisted of 48 sweet sorghum varieties, with 3 grain varieties as controls. Observations focused on agro-morphological parameters and sugar yield components. The results showed a high significance difference between lines for all variables measured except vigor at emergence. On soil with DAP application, 50% of the lines with a cycle of 263 to 273 Julian days had a grain yield higher than 2 t/ha. Only one line (L17) was earlier and more stable in both environments with a cycle of 271 to 273 Julian days. On soil without DAP application, only line L40 had an average yield gain of 2t/ha above the local control (Tieblé). The best performances in sugar concentration were obtained in High-P with 10 lines whose Brix varied from 18% to 20.25% and 15.3% to 17.7% in Low P.